THE EFFECTIVENESS OF ADMINISTERING DEEP BREATH TOWARD PAIN LEVELS ON PATIENTS POST SURGERY - Marsaid, Marsaid; Hidayah, Nurul; Ernawati, Naya (Indonesian Journal of Applied Health, 2024)
Pain is a physiological response arising from one of the postoperative actions. Postoperative actions caused by actual tissue damage make the healing process disrupted. One of the nursing actions for pain management in a non-pharmacological way is administering the deep breathing. This study aims to determine the differences in the effectiveness of pain levels before and after the administration of deep breathing for patients who have TURP surgery at Mardi Waluyo Blitar Hospital. The study design used the quasi-experimental method with the pretest-posttest approach in one group. The sampling technique used was purposive sampling with a total of 10 respondents and treated by controlling a deep breath. The test used is a paired t-test with. The results showed that the treatment was effective in reducing pain levels in patients with TURP Surgery. The effectiveness of controlling deep breath giving p-value = 0.000 with the mean of pain level decreasing about 2.1. That means the use of controlling deep breath treatment can be used as an alternative to reduce the pain of post-TURP surgery.